2010
DOI: 10.1080/02772248.2010.490529
|View full text |Cite
|
Sign up to set email alerts
|

The status of heavy metal levels in a Ramsar site, Kuala Gula bird sanctuary: the impact of the anthropogenic inputs

Abstract: Distributions of Cd, Cu, Pb, and Zn in the surface sediments from two sites of the Kuala Gula Bird Sanctuary, Malaysia were monitored for a period of 6 months from October 2006 to March 2007. In December 2006, the concentration of Zn in one location was significantly ( p50.05) higher (3.9 AE 1.3 mg kg À1 ) than the other metals at both sites, but in the oxidizable organic fraction it was highest at both sites during October; with mean concentrations of 18 mg kg À1 at both locations. In the acid-reducible fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Metals level in the sediment could be one of the important factors that contribute to their accumulation in the animals [22] . For instance, lead level in the surface sediment of Kuala Gula coastal area was reported to be between 12 and 29 ppm [23] and 28–47 ppm [2] which are considerably high. Although moderate correlations between metal levels in sediment and the samples collected were found, they were not significant (p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Metals level in the sediment could be one of the important factors that contribute to their accumulation in the animals [22] . For instance, lead level in the surface sediment of Kuala Gula coastal area was reported to be between 12 and 29 ppm [23] and 28–47 ppm [2] which are considerably high. Although moderate correlations between metal levels in sediment and the samples collected were found, they were not significant (p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphate in Saiburi River might be originated from the irrigation water whereby the continuous use of water in the irrigation system would indirectly release the diluted phosphorus from fertilizer and soil into the stream (Yolthantham, 2007). However, the concentration of phosphorus in this river was not according to the NWQI standard, since it exceeded 0.2mg/l, which is the maximum level for Class II river in Malaysia (Lomoljo et al, 2009).…”
Section: Corbicula Fluminea and Phytoplankton Sampling And Analysismentioning
confidence: 84%
“…The effect of consistent anthropogenic activities, as reported by Rahman et al (2013), was evidenced in the decline of wild Milky Stork population from surface sediment samples in foraging areas. A study by Lomoljo et al (2010) in Kuala Gula bird sanctuary showed lower concentrations of heavy metals due to minimal human activities around the study area (Table 8). However, findings by Lomoljo et al (2010) claimed that even though the concentrations in certain areas might be low, as in the study area (MMFR), it might increase through bioaccumulation.…”
Section: Heavy Metals Concentration In the Sedimentsmentioning
confidence: 93%
“…A study by Lomoljo et al (2010) in Kuala Gula bird sanctuary showed lower concentrations of heavy metals due to minimal human activities around the study area (Table 8). However, findings by Lomoljo et al (2010) claimed that even though the concentrations in certain areas might be low, as in the study area (MMFR), it might increase through bioaccumulation. Therefore, a follow-up study should be conducted to monitor the levels of contamination in the reserve forest.…”
Section: Heavy Metals Concentration In the Sedimentsmentioning
confidence: 93%